2015
DOI: 10.2319/031114-176.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of face mask treatment started simultaneously and after the completion of the alternate rapid maxillary expansion and constriction procedure

Abstract: The null hypothesis was rejected. Both groups showed similar results, and, thus, waiting until completion of the Alt-RAMEC procedure for the FM treatment is not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
3
26
0
1
Order By: Relevance
“…According to Celikoglu and Oktay [16], overjet correction of 5.0 mm by MMP therapy was achieved, and approximately, 66 % of this change was skeletal. In addition, maxillary skeletal contribution to overjet correction was higher than mandibular skeletal contribution in both MMP and FM/RME groups and this finding was in agreement with previous studies [4,16,32,35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to Celikoglu and Oktay [16], overjet correction of 5.0 mm by MMP therapy was achieved, and approximately, 66 % of this change was skeletal. In addition, maxillary skeletal contribution to overjet correction was higher than mandibular skeletal contribution in both MMP and FM/RME groups and this finding was in agreement with previous studies [4,16,32,35].…”
Section: Discussionsupporting
confidence: 93%
“…It has been indicated that the skeletal and dental changes underlying the soft tissue lead to profile changes [4,27,28,35]. Celikoglu and Oktay [16] also reported significant forward movement of the upper lip (2.1 mm) and insignificant backward movement of the lower lip (−0.6 mm) in their study.…”
Section: Discussionmentioning
confidence: 81%
“…Although the efficiency of maxillary protraction with the Alt-RAMEC protocol has been widely investigated in the literature, [18][19][20][21]23,24 none of the previous studies have focused on pharyngeal effects of this method when used for the correction of maxillary retrusion. The groups were well matched for gender distribution, chronological ages, treatment durations, and initial craniofacial and pharyngeal airway measurements as statistically tested, and thus the effects of those factors on findings were eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Liou 18 introduced a method called alternate rapid maxillary expansion (Alt-RAMEC) protocol to increase the skeletal effects of maxillary protraction, and several clinicians [19][20][21] reported the increased skeletal effects of this method when performed prior to maxillary protraction. To our knowledge, none of the previous studies evaluated the effects of maxillary protraction with Alt-RAMEC protocol on pharyngeal airway dimensions and hyoid bone position.…”
Section: Introductionmentioning
confidence: 99%
“…According to this protocol, the maxilla is expanded for 7 consecutive days and constricted for 7 consecutive days for a total 7-9 weeks. (2) Many clinical studies (3,4,5) which combine this technique with facemask were done to evaluate the amount of maxillary protraction after Alt-RAMEC protocol. So the pure effects of Alt-RAMEC could not be evaluated.…”
Section: Introductionmentioning
confidence: 99%